Gestão de transporte intercampi: uma proposta para a Universidade Federal de Goiás - regional Goiânia - Silva, Regina Maria da (2018)
In a context of reformist policies that have been taking place in Brazilian higher education, the process of reordering also includes changes in the institutional identities of universities, in order to meet the multiple local and regional demands. This work is aimed at the area of university transportation offered by the educational institutions themselves, analyzing the forms of intercampi transportation in Brazilian universities and other international studies. The objective of the research is to expose the feasibility of improvement and expansion of the current transportation service in the UFG, starting to offer a fixed and regular traffic line to students and servers. Formulating a new management model, according to the concepts of Banchmarking, we took as reference intermodal transport models existing in other IFES, for integration of all UFG Campuses in the Regional Goiânia, providing greater comfort and safety to the academic community. The methodology used is applied research because it involves local truths and interests. It brings a quantitative approach to understanding, characterizing and analyzing the current processes in the Transportation Division (DT) of UFG. Aiming to detail its operational aspects and present a diagnosis of the functioning of this department, the BPMN method is used with the theory of "AS IS" and "TO BE", elaborating the flowcharts of the activities. The alterations indicated are based on data received from DT referring to values of acquisition and maintenance costs of bus-type vehicles, as well as data on the number of cars trips taken and personnel. With this data a cost forecast was made to implement and execute the suggested transport service. As a result of the research, it presents aspects relevant to the implementation of this service in the UFG and also presents a management model based on the management elements currently used in the transportation sector. Finally, the redesign of the main processes and suggested new methods to perform the activities after the implementation of the proposal are presented, making a synthesis of the activities already practiced and the activities to be added with the implementation of the intercampi. As the main social contribution of this proposal, it is believed that it will be possible to add values to the organization for its academic community, such as: accessibility, security, availability, regularity, reliability, comfort, competence, credibility, courtesy and tangibility.